Improved Understanding of Science Concepts in Terms of the Pattern of Concept Maps Based on Scientific Literacy in Prospective Elementary School Teacher Students - Fina Fakhriyah*; Siti Masfuah; F Shoufika Hilyana; I Gede Margunayasa (Jurnal Pendidikan Sains Indonesia, 2022)
Concept maps are a technique that can represent the knowledge possessed by students. Depiction through concept maps can form a structured and systematic understanding of concepts based on the relationships between the written concepts. In a period of online learning like this, an exciting learning strategy is needed. Therefore, using concept maps can be an alternative learning strategy that lecturers can apply in online learning. This study aims to identify various concept map patterns that students often use to improve conceptual understanding of the topic of global warming as well as increase students' conceptual understanding of the draft concept map patterns. This research is a mixed-method type with concurrent embedded with 83 students of Primary Teacher Education semester 2 of the 2019/2020 academic year. The instrument used was the measurement instrument for the concept map pattern and the measurement of the conceptual understanding test based on scientific literacy for students. The results were then analyzed by normalized N-Gain test and qualitative data analysis. The results showed that students' concept map patterns to improve conceptual understanding using the hub/spokes concept map pattern were 87.9%. Meanwhile, the results of the N-Gain analysis showed several 0.53 (in the medium category), which means that understanding of the concept increases with the application of concept map learning. The concept map pattern that appears depicts the results of the visualization of students' conceptual understanding